2018
DOI: 10.14710/jpki.14.1.68-80
|View full text |Cite
|
Sign up to set email alerts
|

Faktor yang Berhubungan dengan Deteksi Dini Kanker Serviks Metode IVA di Puskesmas Kota Padang

Abstract: Background: In 2013 the prevalence of cervical cancer in West Sumatra was 0.9 per 1000 population. This data exceeds the Indonesian prevalence of 0.8 per 1000 population.  Lack of public knowledge regarding early detection of cervical cancer is the cause of the high prevalence of cervical cancer. This study aims to determine the factors associated with the participation of women of childbearing age in the early detection of VIA method cervical cancer in Padang City Health Center in 2018.Method: This study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 0 publications
0
4
0
6
Order By: Relevance
“…This result is in line with research in 2018 which states that, based on statistical tests obtained a value of <0.05, it can be concluded that there is a significant relationship between the level of knowledge and the participation of WUS in the early detection of cervical cancer using the IVA method. This can be because the level of knowledge is a predisposing factor that facilitates or dispositions the occurrence of a person's health behavior, namely participation in early detection of cervical cancer using the IVA method [20].…”
Section: Knowledge Relationship With Early Detection Of Cervical Cancer Iva Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in line with research in 2018 which states that, based on statistical tests obtained a value of <0.05, it can be concluded that there is a significant relationship between the level of knowledge and the participation of WUS in the early detection of cervical cancer using the IVA method. This can be because the level of knowledge is a predisposing factor that facilitates or dispositions the occurrence of a person's health behavior, namely participation in early detection of cervical cancer using the IVA method [20].…”
Section: Knowledge Relationship With Early Detection Of Cervical Cancer Iva Methodmentioning
confidence: 99%
“…WUS must not only have a good level of knowledge regarding the early detection of cervical cancer using the IVA method, but it must also be reflected in attitudes. WUS with a positive attitude will affect the desire of WUS to want to carry out early detection of cervical cancer using the IVA method [20].…”
Section: Relationship Between Attitude and Early Detection Of Cervical Cancer Methods Ivamentioning
confidence: 99%
“…Pengetahuan yang dimiliki oleh sesorang tentang suatu penyakit akan secara tidak langsung bahwa seseorang tersebut akan melakukan pencegahan (5). Kurangnya pengetahuan pada WUS dalam kategori kurang baik tentang kanker serviks dan deteksi kanker serviks juga terlihat dari responden pada penelitian sebelumnya yang pada dasarnya responden tidak mengerti faktor yang menyebabkan wanita mengalami kanker serviks (6). Dalam penelitian ini, peneliti menyimpulkan bahwa pengetahuan yang didapatkan bahwa banyak sekali responden yang belum tahu dan ada beberapa yang belum mengetahui apa itu kanker serviks dan bagimana cara pencegahan awalnya dengan nilai rata-rata sebelum dilakukan pendidikan kesehatan tentang kanker serviks adalah 9,09.…”
Section: Pembahasan Pengetahuan Kanker Serviks Wus Sebelum Diberikan Pendidikan Kesehatanunclassified
“…Berdasarkan data dari World Health Organization (WHO) pada tahun 2014 terdapat lebih dari 528.000 kasus baru dan 266.000 kasus kematian di seluruh dunia akibat kanker serviks pada wanita dengan usia 15 -44 tahun. Menurut data dari Kementrian Kesehatan Republik Indonesia (Kemeskes RI) pada tahun 2013, kejadian kanker serviks di Indonesia sebesar 0,8% [2]. Jawa Barat merupakan provinsi dengan jumlah penduduk terbanyak di Indonesia yaitu 40.737.594 orang, dimana penduduk wanita sebanyak 49,5% dan terdapat angka kejadian tumor/kanker 0,5% estimasi kejadian 26/100.000 wanita atau sekitar 5200 kasus [3].…”
unclassified
“…Selain itu, IVA tidak memerlukan infrastruktur yang terlalu sulit, murah, mudah, dan cepat diketahui hasilnya. Metoda skrining ini memang dapat memberikan hasil positif palsu yang cukup besar karena sangat subjektif dari penilaian pelaksana [2], [5]. Untuk menekan angka positif palsu, dikembang suatu aplikasi berbasis pengolahan citra digital dalam deteksi dini kanker serviks.…”
unclassified